The dynamics of recruitment, selection, and election of neophyte politicians in Iloilo City - Meren, Christcelle Enriquez; Palmani, Kritine michelle Oquendo; Ibabao, Rhodella (Miagao, Iloilo University of the Philippines in the Visayas, 2005)
This study is an introspection on the factors that helped neophyte politicians penetrate the political arena of Iloilo City. This study explores and analyzes political recruitment, selection process, and election mechnaisms in line with the various theories in these three(3) identified concepts established by scholars in the discipline of political science., This study was conducted in October 2004 to February 2005 in Iloilo City, which is composed of six (6) districts namely Jaro, Lapaz, Mandurriao, Molo, Arevalo, and Iloilo City Proper. Structured interview schedules were utilized to gather relevant information from eight (8)key informants who directly participated in the recruitment pattern, slection process, and election conduct in the May 2004 election. Documents from COMELEC, Sangguniang Panlungsod, and articles from archival research and library materials were also utilized. The recruitment pattern of neophyte politicians in Iloilo City significantly varies depending on the kind of organizational and political networks in which they were identified. The traditional source of local leadership, which is the local elite political family, was challenged by the emergence of new recruits that constitute the new political players who belong to middle class professional and entrepreneurs. A notable observation was recruitment from a non-political source, which is media popularity. In the selection process, neophyte politicians join political parties for political convenience. Neophyte politicians who are proteges of top party line-up. the conduct of electoral campaign of neophyte politicians included new campaign strategies and techniques, however it was apparent that neophyte politicians gave in to the traditional campaigning method.
Research Study (Undergraduate, Bachelor of Arts in Political Science) -- Miagao, Iloilo : University of the Philippines in the Visayas, March 2005.
Keywords: Politicians -- Neophytes